Instructional Communication Resilience: Sustaining Sakinah Family Values Amidst Modern Marital Disruption - Saini; Rizkiana Amalia; Fifi Alaida Nurul Alawiyah (Al-Insan: Islamic and Humanities Perspectives Journal, 2026)
The increasing rate of divorce in various regions reflects a disruption in marital relationships that contributes to family vulnerability. This study aims to analyze the phenomenon of marital disruption and examine the educational communication strategies employed by religious counselors to internalize sakinah family values in Sukowono District, Jember Regency. This research adopts a qualitative approach with a case study design. Data were collected through in-depth interviews with religious counselors, the head of the Office of Religious Affairs (KUA), and couples participating in premarital guidance programs, complemented by field observations and document analysis. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion verification. The findings indicate that marital disruption in Sukowono is shaped by three main factors: weak interpersonal communication between spouses, limited psychological readiness for marriage, and changing communication patterns influenced by digital technology. To address these challenges, religious counselors apply instructional communication strategies through dialogical interaction, persuasive, value-based religious communication, empathetic counseling, and adaptive communication approaches. This study proposes the concept of instructional communication resilience as a model for strengthening sakinah family development through educational communication within community-based religious institutions.